Expanding methods to address RE-AIM metrics in hybrid effectiveness-implementation studies - Samantha M. Harden; Karla I. Galaviz; Paul A. Estabrooks (Implementation Science Communications)
Abstract Background Dissemination and implementation science is an evolving field that focuses on the strategies and mechanisms by which scientific evidence is adopted, used, and sustained in clinical and community practice. Main body Implementation scientists are confronted by the challenge to balance rigor and generalizability in their work while also attempting to speed the translation of evidence into clinical and community practice. Hybrid Effectiveness-Implementation studies and the RE-AIM framework were conceptualized to address these challenges. Hybrid Effectiveness-Implementation (HEI) studies provide methods of examining the effectiveness of health promoting interventions while concurrently assessing the utility of dissemination and implementation strategies designed to enhance the application of evidence-based principles in practice. RE-AIM provides a set of planning and evaluation dimensions that can be assessed with a goal to balance internal and external validity. The purpose of this commentary is to provide clarity on definitions of each approach and how to effectively use them together to answer research questions that will advance dissemination and implementation science for health promotion. Conclusions We provide examples of concerted use of RE-AIM within HEI studies from the literature and focus on language to provide a clarity and consistency across research questions, designs, and settings. We share how to operationalize RE-AIM dimensions in HEI studies for both dissemination and implementation strategies. Future directions include refining, defining, and evaluating each RE-AIM dimension within hybrid studies.